Naravne oblike gibanja – temelj gibalnih dejavnosti v predšolskem obdobju - Videmšek, Mateja (Šport (Ljubljana), 2021)
In this paper, we present natural forms of movement for preschool children, which are extremely important in this period due to their positive impact on all areas of development. We have defined didactic recommendations and special features that we must take into account in their organization and implementation, and we have proposed sports aids and toys suitable for younger children, with the help of which they can spread their knowledge from other fields as well. In the pre-school period, children should gain a variety of experiences by performing natural forms of movement, especially through play, which brings them joy and satisfaction.
Keywords: didactic recommendations; didaktična priporočila; gibalni razvoj; movement development; naravne oblike gibanja; natural forms of movement; predšolski otroci; preschool children; sport; sports equipment; šport; športna tehnologija